Risk Factors for Pulomonary Tuberculosis in Adult in the Municipality of Bobonaro, Timor Leste - Eugenia Borges; RR Sri Ratna Rahayu; Yuni Wijayanti (Science Tech Group, 2026)
The prevalence of Pulmonary Tuberculosis in the Municipality of Bobonaro, Timor Leste, is still relatively high and requires serious attention in efforts to control infectious diseases. This study aims to analyze risk factors related to the incidence of Pulmonary Tuberculosis in adults. This study uses a quantitative approach with a case-control design and was conducted in June–July 2025. The sample consisted of 95 cases and 95 purposively selected controls. Data were analyzed using SPSS version 30. The results showed that smoking history was the most dominant factor with a risk of 6.685 times (p < 0.001), followed by occupancy density (OR = 4.313; p < 0.001), firewood use (OR = 3.515; p = 0.003), alcohol consumption (OR = 3.494; p = 0.002), inadequate home ventilation (OR = 3.061; p = 0.007), and history of close contact (OR = 2.667; p = 0.018). Nutritional status factors (OR = 1.916) and access to health services (OR = 2.135) showed risky but not significant trends. These findings emphasize the importance of interventions on behavioral and environmental factors in TB control strategies in Bobonaro.